Human Pluripotent Stem Cells Differentiated in Fully Defined Medium Generate Hematopoietic CD34(+) and CD34(−) Progenitors with Distinct Characteristics - Chicha, Laurie (Public Library of Science, 2011)
BACKGROUND: Differentiation of pluripotent stem cells in vitro provides a powerful means to investigate early developmental fates, including hematopoiesis. In particular, the use of a fully defined medium (FDM) would avoid biases induced by unidentified factors contained in serum, and would also allow key molecular mediators involved in such a process to be identified. Our goal was to induce in vitro, the differentiation of human embryonic stem cells (ESC) and induced pluripotent stem cells (iPSC) into morphologically and phenotypically mature leukocytes and erythrocytes, in the complete absence of serum and feeder cells. METHODOLOGY/PRINCIPAL FINDINGS: ESC and iPSC were sequentially induced in liquid cultures for 4 days with bone morphogenic protein-4, and for 4 days with FLT3-ligand, stem cell factor, thrombopoietin and vascular endothelium growth factor. Cell differentiation status was investigated by both mRNA expression and FACS expression profiles. Cells were further sorted and assayed for their hematopoietic properties in colony-forming unit (CFU) assays. In liquid cultures, cells progressively down-modulated Oct-4 expression while a sizeable cell fraction expressed CD34 de novo. SCL/Tal1 and Runx1 transcripts were exclusively detected in CD34(+) cells. In clonal assays, both ESC and iPSC-derived cells generated CFU, albeit with a 150-fold lower efficacy than cord blood (CB) CD34(+) cells. ESC-derived CD34(+) cells generated myeloid and fully hemoglobinized erythroid cells whereas CD34(−) cells almost exclusively generated small erythroid colonies. Both ESC and iPSC-derived erythroid cells expressed embryonic and fetal globins but were unable to synthesize adult β-globin in contrast with CB cells, suggesting that they had differentiated from primitive rather than from definitive hematopoietic progenitors. CONCLUSIONS/SIGNIFICANCE: Short-term, animal protein-free culture conditions are sufficient to sustain the differentiation of human ESC and iPSC into primitive hematopoietic progenitors, which, in turn, produce more mature blood cell types. However, additional factors have yet to be identified to allow their differentiation into definitive erythroid cultures.